Peningkatan Mutu dan Diversifikasi Olahan Pangan Berbasis Singkong Untuk Menunjang Penguatan Ekonomi Perempuan Purna Pekerja Migran dan Korban Kekerasan dalam Rumah Tangga - Mokhamad Nur (Journal of Innovation and Applied Technology, 2022)
A lot of retired migrant female worker face many problems, both before and during as well as after stopped being a migrant worker and came back home. Some of the problems are unemployment, family problems, exploitation, discrimination, and domestic violence. Singkong Jaya Women Community is built to overcome those problems through various empowerment programs. The aim of this Doktor Mengabdi program is to increase the quality and product diversification that produced by Singkong Jaya Women Community which is located in Sukowilangun village, Kalipare district, Malang regency. In accordance to the previous year study, there are several problems identified, such as the lack of facilities and modals, product packaging and marketing as well as license or marketing certificate. To overcome those problems, this community service program has done mentoring programs, training and tools assistance, in order to increase the quality of the product.